1988
DOI: 10.1128/iai.56.6.1532-1537.1988
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunogenic outer membrane proteins of Pasteurella multocida 3:A in rabbits

Abstract: Four groups of protective rabbit immune sera were used to identify Pasteurella multocida outer membrane immunogens by a radioimmunoprecipitation procedure and Western blot (immunoblot) analysis. These are rabbit hyperimmune sera against KSCN extract of P. multocida (group 1) and rabbit immune sera against the KSCN extract of P. multocida (group 2), the outer membrane of P. multocida (group 3), and live P. multocida cells (group 4). Rabbits mounted an antibody response to 18 proteins found in the outer membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 21 publications
1
17
1
2
Order By: Relevance
“…Preparation of P. multocida outer membranes. The outer membranes were prepared as described previously (11). The capsules of the organisms were removed enzymatically with hyaluronidase (11), since type A P. multocida is known to contain hyaluronic acid (3).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preparation of P. multocida outer membranes. The outer membranes were prepared as described previously (11). The capsules of the organisms were removed enzymatically with hyaluronidase (11), since type A P. multocida is known to contain hyaluronic acid (3).…”
Section: Methodsmentioning
confidence: 99%
“…(iv) Purification of antibodies against P. multocida OMP. For determination of whether antibodies against OMP were the protective components of the immune sera, the effluent immune sera were adsorbed with intact P. multocida cells and the antibodies were eluted from the cell-antibody complex (11). In brief, freshly cultured homologous P. multocida cells (108 CFU in 0.5 ml of PBS) were mixed with an equal volume of serum and incubated for 1 h at 4°C with gentle agitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies on the P. multocida outer membrane showed that a 37 kDa protein was among five identified as possible protective immunogens based firstly on radioimmunoprecipitation results using protective immune rabbit sera, and secondly on their location in the outer membrane (Lu et al, 1988). Monoclonal antibodies raised against the 37 kDa protein were able to passively protect rabbits and mice against infection with P. multocida with strong protection afforded against homologous strains, and some limited protection against heterologous strains (Lu et al, 1991).…”
Section: Outer Membrane Proteinsmentioning
confidence: 99%
“…The immunoblot results and the N-terminal homologies suggest that p40 and p42 are at least related to porin proteins. Sarcosyl insoluble proteins are known to be OMPs, cell-surface exposed, and therefore accessible to antibodies (LUGTENBERG et al, 1986;LU et al, 1988). In addition to their capability of forming water-filled trans-outer-membrane channels (porins), which permit the passage of small hydrophilic molecules, OMPs, particularly MOMPs, are probably also involved in the infectious process.…”
Section: Amino-terminal Sequencingmentioning
confidence: 99%